2024
DOI: 10.1002/ksa.12022
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative joint line obliquity, a newly identified factor for overcorrection, can be incorporated into a novel preoperative planning method to optimise alignment in high tibial osteotomy

Se‐Han Jung,
Min Jung,
Kwangho Chung
et al.

Abstract: PurposeThe aim of this study was to analyse the factors associated with additional postoperative alignment changes after accurate bony correction by selecting only patients with well‐performed bony correction as planned and develop a method of incorporating significant factors into preoperative planning.MethodsAmong 104 consecutive patients who underwent medial open wedge high tibial osteotomy (MOWHTO) between October 2019 and July 2022, 61 with well‐performed bony corrections were retrospectively reviewed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…It was reported that the preoperative JLCA on standing position and joint line obliquity could be used to estimate additional alignment changes [ 12 ]. Recently, knee deformities have been assessed using three‐dimensional computed tomography (CT).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the preoperative JLCA on standing position and joint line obliquity could be used to estimate additional alignment changes [ 12 ]. Recently, knee deformities have been assessed using three‐dimensional computed tomography (CT).…”
Section: Discussionmentioning
confidence: 99%